The Tooty Fruity Vegie project: Changing knowledge and attitudes about fruits and vegetables - Sallie A. Newell; Anna D. Huddy; Jillian K. Adams; Margaret Miller; Libby Holden; Uta C. Dietrich (Elsevier, 2004)
Abstract Objectives: The Tooty Fruity Vegie (TFV) project was a multi‐strategic, school‐based intervention aimed at preventing the large decline in fruit and vegetable intake that typically starts during primary school. Methods: During 1999 and 2000, TFV was implemented in 10 volunteer primary schools across the Northern Rivers region of New South Wales. Surveys were conducted, in late 2000, with children, parents, teachers and principals across nine intervention and three matched control schools. Intervention schools' management teams also completed strategy implementation indexes indicating how often, how well and with how many people each major strategy was implemented. Results: Completed surveys from 613 parents (59%), 392 older children (65%), 5C teachers (81%) and all 10 intervention principals and school management teams showed the project was well implemented, achieved high reach and was very positively received. The project enhanced the quality, diversity and frequency of classroom fruit and vegetable‐promoting activities, substantially increasing children's involvement and enjoyment levels. It significantly improved children's fruit and vegetable knowledge, attitudes, access and preparation skills; parents' knowledge and involvement in fruit and vegetable‐promoting activities in schools and beyond; and teachers' perceived support for doing fruit and vegetable promotions. Conclusion: Despite some methodological limitations, which may limit confidence in our findings, survey results across all target groups consistently indicated that primary schools can be supported to establish, implement and sustain highly acceptable and effective fruit and vegetable‐promoting programs.